Global Burden of Bacterial Skin Diseases: A Systematic Analysis Combined With Sociodemographic Index, 1990–2019 - Xue, Yi; Zhou, Jie; Xu, Bei-Ni; Li, Yue; Bao, Wu; Cheng, Xia Lin; He, Yan; Xu, Chun Peng; Ren, Jun; Zheng, Ya rong; Jia, Chi Yu (Frontiers in Medicine, 2022)
Background The latest incidence and disability-adjusted life-years (DALYs) of major bacterial skin diseases (BSD) and their relationship with socioeconomic are not readily available. Objective Describe the global age-standardized incidence and DALYs rates of BSD and analyze their relationship with socioeconomic. Methods All data were obtained from Global Burden of Disease (GBD) 2019 database. The correlation between BSD and socioeconomic development status was analyzed. Results The age-standardized incidence and age-standardized DALYs rate of BSD are: 169.72 million [165.28–175.44] and 0.41 million [0.33–0.48]. Of the two main BSD, pyoderma cause significantly much heavier burden than cellulitis. The change of age-standardized incidence (7.38% [7.06–7.67]) and DALYs (−10.27% [−25.65 to 25.45]) rate of BSD presented an upward or downward trend from 1990 to 2019. The highest burden was in the low-middle sociodemographic index (SDI) area while the area with the lowest burden was recorded in the high-middle SDI area in 2019. Limitations GBD 2019 data of BSD are derived from estimation and mathematical modeling. Conclusion The burden of BSD is related to socioeconomic development status. The results based on GBD2019 data may benefit policymakers in guiding priority-setting decisions for the global burden of BSD.